Asuhan Keperawatan Pada Pasien Isolasi Sosial Dengan Fokus Tindakan Terapi Aktivitas Kelompok Sosialisasi (Taks) Sesi 1: Memperkenalkan Diri - Zalzabilla Diah Saputri; Christina Trisnawati; Fida Dyah Puspasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Backround: mental health is a stase of emotional, psychological and social health that can be seen in satisfying interpersonal relationships, effective behavior and copinh, posifive self concept and emotional stability. Social isolation is a lonely state experienced by someone because other people express a negative and threatening attitude. Socialization group activity therapy is a therapy that is carried out in grops to improve the patients ability to carry out social interaction and play a role in the social environment. Objective:this case studies to determine nursing care for social isolation patients with a focus socialization group activity therapy session 1: introducing yourself. Methods: data collection methods used descriptive analysis and case studies. Results:after carrying out nursing actions for 3 days and giving socialization group activity therapy session 1, Mr. T was able to defend himself.  Conclusions: giving socialization group activity therapy session 1: introducing yourself is very effective for patients with sosial isolation.